UNIDO—Agency for industrial development - Samuel Lurié (Intereconomics, 1969)
Together with the growing urgency of industrial development in the developing countries, the United Nations Industrial Development Organisation (UNIDO) is also more and more in the focus of interest. This young organisation, which two and a half years ago with much ambition assumed a huge bouquet of tasks, is—as all other bodies, loo-facing various difficulties as for instance where to concentrate activities, where to get the financial means, and last but not least how to please all parties concerned at the same time. What UNIDO's activities under such a general head term as ,,industrial development” are, which problems are emerging and what the strategy of UNIDO in the Second Development Decade will be told us Dr Samuel Lurié, whom we visited in Vienna on occasion of the third meeting of the Industrial Development Board, the directive body of UNIDO.
Keywords: 330; Interview